Fatores de risco para a mortalidade neonatal precoce em Sergipe, entre 2011 e 2016 : estudo de linkage - Oliveira, Daya Devi Souza de (2018)
Introduction: every year millions of children die worldwide, mainly due to preventable causes, infant mortality is a key tracer of quality of life and health services, which reveals the conditions of social, political and ethical well-being of a population. Objectives: To describe the risk factors associated with early neonatal mortality from the linkage between the information of live births registered in the SINASC in Sergipe in the period from 2011 to 2016 and the respective early neonatal deaths recorded in the SIM. Methodology: a retrospective cohort study using data from live births recorded in the SINASC, where a deterministic linkage was performed with data on early neonatal deaths recorded in the SIM. Results: in all were 205,042 live births between the period of 2011 and 2016, of these 203,334 survived and 1708 died. Regarding the variables analyzed regarding the mother, risk was found in adolescent mothers with advanced maternal age. As for the variables in gestation at delivery, there was a risk for adequate prenatal care, at preterm gestational age, at home, at vaginal delivery and without labor induction. For the variables associated with the newborn, APGAR of the 5th minute was lower than 7, birth weight less than 2500 g and for the presence of congenital anomaly. Conclusion: the main risk factors for early neonatal mortality in Sergipe were evidenced in this study; presented a risk factor for adolescent and advanced maternal age, vaginal delivery, very preterm gestational age, extreme low birth weight, Apgar score on the 5th critically low, and the presence of congenital malformation. Protective effect for brown / black race and maternal schooling.